Diazoxide for the Treatment of Transitional Neonatal Hypoglycemia: A Systematic Review. Issue 4 (December 2021) - Laing, Don; Hanning, Sara M; Harding, Jane E; Mravicich, Lisa C; McKinlay, Christopher JD
Background: Neonatal hypoglycemia is widely recognized as a common, preventable cause of brain injury in infants. Early use of diazoxide, which attenuates insulin secretion, is a possible treatment strategy for neonates that fail first-line management of hypoglycemia. Objective: To systematically evaluate the effectiveness and safety of diazoxide compared to placebo or no diazoxide treatment for improving short- and long-term outcomes in neonates born at ≥35 weeks' gestation who require treatment for transitional hypoglycemia. Methods: MEDLINE, SCOPUS, EMBASE, and Cochrane databases were searched from inception until November 2020. We included all published randomized and nonrandomized controlled studies of diazoxide therapy in neonates that reported 1 or more prespecified outcomes. We excluded studies that primarily reported on neonates born at <35 weeks, with congenital hyperinsulinism or inborn errors of metabolism, or who started treatment after 1 month of age. Two authors independently performed screening, risk of bias assessment, data extraction, and rating of evidence certainty (GRADE). Meta-analysis was performed in RevMan (inverse variance, fixed effects). Results: A total of 161 studies were screened, 7 reviewed in full, and 1 included (N = 30). Low-certainty evidence suggested that diazoxide, compared with placebo, is associated with a shorter duration of intravenous fluids (mean difference [MD] –50 h, 95% confidence interval [CI] −94, −6), decreased time to achieve full enteral feeding (MD –49 h, 95% CI −91, −7), and euglycemia (MD –33 h, 95% CI −66, −0). Conclusions: Diazoxide may promote metabolic transition in late preterm and term neonates with transitional hypoglycemia. Further high-quality randomized trials are needed to assess short- and long-term effects of diazoxide therapy.